Square-Framed T Shape mmwave Antenna Array at 28 GHz for Future 5G Devices - Saad Hassan Kiani; Xin Cheng Ren; Adil Bashir; Ammar Rafiq; Muhammad Rizwan Anjum; Mian Muhammad Kamal; Burhan Ud Din; Fazal Muhammad (International Journal of Antennas and Propagation)
In this research, a novel T shape antenna is proposed for millimetre-wave (mmwave) 5G systems. Designed on 0.254 mm thin Roggers 5880 substrate with a dielectric constant of 2.3 and the loss tangent of 0.0009, the proposed antenna offers a wideband characteristics of nearly 8 GHz with gain of 4.25 dBi for single element. Based on these characteristics, the single element is further constructed into a four-element linear array with a compact size of 18.5 × 24 mm2 The proposed antenna array exhibited dual beam radiation patterns with a high realized gain of 11.5 dBi and 94% efficiency. The measured results from the fabricated prototype well agree with the simulated results and thus, therefore, make the proposed antenna system a well-suited candidate for future mmwave devices.